Pengaruh Metode Sima’ah Terhadap Prestasi Hafalan Al-Qur’an pada Siswa Program Tah’fidz Sekolah Menengah Pertama Muhammadiyah 1 Surakarta Tahun Ajaran 2023/2024 - Andi Zulfikar Musa; Imam Suhadi; Yetty Faridatul Ulfah (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This study aims to determine whether there is an influence between the Sima'ah Method on the Achievement of Memorizing the Qur'an in Students of the Tah'fidz Program at Muhammadiyah 1 Surakarta Junior High School. The sima'i method is a method of teaching verses that have not been memorized and repeating memorization to strengthen and facilitate. The achievement of memorizing the Qur'an is the result obtained by individuals in collecting many words, sentences or verses of the Qur'an in their minds. This type of research is quantitative and includes correlation studies. The population studied was students of the tahfidz program at Muhammadiyah 1 Surakarta Junior High School, totaling 66 people. The researcher used a questionnaire to collect data. The researcher used a descriptive statistical method. The results of the study showed that (1) The sima'ah method, obtained the majority results of 36 respondents with a percentage of 54.5% whose value was in the moderate category (2) Memorization achievement, obtained the majority results of 38 respondents with a percentage of 57.6% who were in the moderate category, (3) There is an influence of the sima'ah method on the memorization achievement of the Al-Qur'an of students in the tahfidz program at SMP Muhammadiyah 1 Surakarta. This is known from the results of the hypothesis test analysis using the product moment technique, the calculated r value was 0.388, while the r table value was 0.244. At a significance level of 5%, namely 0.388 > 0.244.